Sequential analysis of soil factors related to common scab of potatoes - Sagova-Mareckova, M; Omelka, M; Kopecky, J (FEMS microbiology ecology, 2017)
The severity of common scab (CS) of potatoes has been correlated with multiple environmental factors. This study aimed at separating the effect of factors related to local conditions from those correlated to the disease development at all studied sites using a mathematical adjustment of the variables' means for site and field. The experiment was conducted at two sites differing in soil conditions, where a field with low disease severity occurs next to one with high severity. Three cultivars susceptible to CS were grown in four replicates on each field. Bacteria, actinobacteria and the txtB gene, involved in the biosynthesis of the main CS pathogenicity factor, thaxtomin, were quantified by real-time PCR. Bulk soil, tuberosphere soil and potato periderm were characterized by carbon, nitrogen, phosphorus, sulfur, calcium, magnesium and iron contents. The adjustment of the data for field effects eliminated the confounding local conditions and showed that at all fields the CS severity was negatively correlated with soil S content while the number of txtB gene copies was positively correlated with soil C and N contents. Thus, those factors might have a more general relationship to the pathogen occurrence and disease severity, which needs to be verified in other environmental conditions.
Keywords: thaxtomin; Soil; qPCR; soil nutrients; půdní mikrobiologie; Soil Microbiology; Solanum tuberosum; Streptomyces; kvantitativní polymerázová řetězová reakce; Bacteria; Real-Time Polymerase Chain Reaction; půda; nemoci rostlin; Plant Diseases